2021
DOI: 10.3390/ma14185379
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Road Performance of Foamed Warm-Mixed Reclaimed Semi-Flexible Asphalt Pavement Material

Abstract: Warm-mixed reclaimed asphalt pavement (RAP) technology has been widely studied worldwide as a recycled environmental method to reuse waste materials. However, the aggregate skeleton structure of the warm-mixed reclaimed asphalt mixture is not stable because of the existence of the recycled materials. Warm-mixed recycled semi-flexible pavement material can solve the defects of the above materials. In this study, five different types of open-graded asphalt mixtures containing different contents of RAP were desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Xie [40] analyzed the grey correlation of various road performance factors with warmmix recycled semi-flexible materials. It was found that the multiple factors have different degrees of influence on the road performance of warm-mix recycled semi-flexible materials and that these factors constrain each other.…”
Section: Grey Correlation Analysis Methodsmentioning
confidence: 99%
“…Xie [40] analyzed the grey correlation of various road performance factors with warmmix recycled semi-flexible materials. It was found that the multiple factors have different degrees of influence on the road performance of warm-mix recycled semi-flexible materials and that these factors constrain each other.…”
Section: Grey Correlation Analysis Methodsmentioning
confidence: 99%
“…Based on the above analysis, there existed a certain regularity in the chemical components and rheological properties of asphalt during aging. Concerning existing studies, the grey relation theory [41,42] was introduced in this study to analyze the molecular rheological properties. The grey relation theory can be used to analyze data based on a small sample and poor information and to describe the relationship between each factor and the system development in terms of degree.…”
Section: Grey Correlation Analysis Of Molecular Components and Rheolo...mentioning
confidence: 99%
“…In recent years, China has strengthened the research on semi-flexible pavement materials, and some cities have paved semi-flexible pavement test sections, such as Quanzhou, Nanjing, Suzhou, etc. These test sections have proved that road performance of the semi-flexible material was excellent [14]. At present, the research on semi-flexible pavement materials mainly focuses on the mix design of matrix asphalt mixture and high-performance cement grouting material [15][16].…”
Section: Introductionmentioning
confidence: 97%